2023
DOI: 10.1111/jog.15759
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on endometrial receptivity: A comprehensive overview of etiology and treatment

Takehiro Hiraoka,
Yutaka Osuga,
Yasushi Hirota

Abstract: Recurrent implantation failure (RIF) remains a challenging problem in assisted reproductive technology (ART). Further insights into uterine abnormalities that can disturb embryo implantation should be obtained. This review provides an overview of the effects of organic and non‐organic uterine disorders on endometrial receptivity. The results suggest that various uterine pathologies can lead to defective embryo implantation via multiple mechanisms. In particular, uterine adenomyosis dysregulates molecular and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 159 publications
(315 reference statements)
0
4
0
Order By: Relevance
“…The live birth rate in the study group was almost double that of control group 1, indicating a substantial improvement in outcomes through personalized approaches [14].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The live birth rate in the study group was almost double that of control group 1, indicating a substantial improvement in outcomes through personalized approaches [14].…”
Section: Discussionmentioning
confidence: 85%
“…The pregnancy rate, implantation rate, and live birth rate were significantly higher in the study group compared to control group 1, highlighting the efficacy of ERA in optimizing reproductive outcomes. The live birth rate in the study group was almost double that of control group 1, indicating a substantial improvement in outcomes through personalized approaches [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, the blastocyst attaches to the receptive endometrium, which is known as adhesion, and finally, the attached blastocyst invades the endometrial stroma by crossing through the endometrial epithelial basement membrane, a process known as invasion. 128…”
Section: Epigenetic Processes Direct Embryo Developmentmentioning
confidence: 99%
“… 47 50 51 52 Studies have suggested that Lactobacillus -dominated endometrial microbiota may improve reproductive outcomes; however, conflicting reports have been published. 49 53 54 55 56 57 58 Imbalances in endometrial microbiota are linked to various reproductive issues, including repeated implantation failure (RIF), pregnancy loss, endometriosis, endometritis, endometrial polyps, hyperplasia, and endometrial cancer (EC). 49 59 60 61 62 63 For instance, Fusobacterium infection of the endometrium causes inflammation, leading to conditions such as endometriosis.…”
Section: The Role Of the Microbiota In Reproductive Healthmentioning
confidence: 99%